ANALISIS KEMAMPUAN BERBICARA BAHASA INDONESIA PADA SISWA-SISWI SDN NO. 20/I JEMBATAN MAS KECAMATAN PEMAYUNG KABUPATEN BATANGHARI KOTA JAMBI - Cici Cici arlin manja (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
The purpose of this study is to analyze in-depth the Indonesian language speaking skills of students in a formal learning context, encompassing linguistic and non-linguistic aspects, such as pronunciation accuracy, intonation, comprehension choices, sentence structure, fluency, and the ability to convey ideas coherently, clearly, and communicatively. This study aims to obtain a comprehensive picture of students' level of speaking skills, the types of errors that frequently occur, and the factors that influence these speaking skills. The results can then be used as a basis for designing more effective strategies, methods, and evaluations of Indonesian language learning that focus on improving oral communication skills.